Peran Guru Mata Pelajaran PPKn dalam Meningkatkan Kedisiplinan Peserta Didik di SMKN 1 Pagerwojo Kabupaten Tulungagung - Intan Fitroh Kurnia; Hikmah Eva Trisnantari (Jurnal Simki Postgraduate, 2024)
Teachers or educators are the spearhead in an educational process. Therefore, teachers have a central role in the successful implementation of educational programs. The role of the teacher is really needed to discipline students which must start with a disciplined teacher. The teacher's task is not only limited to conveying lesson material, but more than that, the teacher must be able to shape students' competence and personality. Teachers must always supervise their students so that there are no deviations in behavior or undisciplined actions by students. So, for this purpose, in order to discipline students, teachers must be able to be mentors, have a strong, stable, authoritative personality and can be an example or role model in the school and community. The researcher conducted this research in the Civics learning process implemented at SMKN 1 Pagerwojo, Tulungagung Regency, to find out the role of Civics subject teachers in improving student discipline in the research school using qualitative research methods, namely the observation, interview and documentation stages, then the data analysis, namely using data reduction, data presentation, drawing conclusions and checking the validity of the data. Teachers provide motivation and guidance to students in overcoming personal, academic, or social problems. They listen, provide advice, and assist students in making informed decisions.